OBT Optical Burst Transport in metro area networks. - Jaedon Kim (IEEE Communications magazine)
For the past few years, the evolution of electro-optical technology has driven change in optical networks in the access and backbone areas. Optical bypassing and traffic aggregation mitigate the scalability problem in backbone networks, and burst mode transmission can provide a cost-efficient solution for access networks. Using those technologies, a new solution can be found for metro area networks, which interconnect access and backbone networks. In this article, we introduce a new solution for metro area networks, called optical burst transport (OBT). OBT is designed to use the promising technologies of backbone and access networks so that it provides all benefits, such as dynamic bandwidth provisioning, scalability, and robustness for unbalanced traffic. The performance evaluation of OBT also is verified by means of a testbed implementation.